2017 Outstanding Contributions to ISCB Award: Fran Lewitter - Fogg, Christiana N. (F1000Res, 2017)
The Outstanding Contributions to the International Society for Computational Biology (ISCB) Award was launched in 2015 to recognize individuals who have made lasting and valuable contributions to the Society through their leadership, service, and educational work, or a combination of these areas. Fran Lewitter is the 2017 winner of the Outstanding Contributions to ISCB Award and will be recognized at the 2017 Intelligent Systems for Molecular Biology (ISMB)/European Conference on Computational Biology, meeting in Prague, Czech Republic being held from July 21-25, 2017.